Evaluasi Program Kampung Zakat Baznas dengan Menggunakan Logic Model - Pratiwi, Nurul; Lutfi, Mukhtar; Haddade, Abdul Wahid (Al-Jadwa: Jurnal Studi Islam, 2024)
Bulukumba is one of the areas designated as the location of the zakat village program which has been running for four years. Therefore, the program needs to be evaluated to measure the effectiveness of the program. This evaluation uses the Logic Model. This study aims to evaluate the Baznas zakat village program in Kahayya Village, Bulukumba Regency using the Logic Model. This research uses mixed methods research. The purpose of this research is to evaluate the Input, Activity, Output, Outcome of Kampung Zakat program in Kahayya Village. The results showed that in the baznas zakat village program in Kahayya Village, various activities were carried out such as providing direct assistance to people in need, training and workshops to improve skills and knowledge, socialization and guidance in various fields such as education, health, economy, da'wah, and humanity. In addition, there are also ben˙cana response activities, procurement of facilities and infrastructure, and efforts to empower communities through various productive economic programs. Statistical test results show that there is a significant difference in the amount of mustahik income before and after the Kahayya Village zakat village program and there is a significant relationship between the length of time receiving assistance and the amount of zakat assistance with the amount of income after the zakat village program in Kahayya Village.